Mechano-induced cell metabolism disrupts the oxidative stress homeostasis of SAOS-2 osteosarcoma cells - Fanelli, Giuseppina; Alloisio, Giulia; Lelli, Veronica; Marini, Stefano; Rinalducci, Sara; Gioia, Magda (Frontiers in Molecular Biosciences, 2024)
There has been an increasing focus on cancer mechanobiology, determining the underlying-induced changes to unlock new avenues in the modulation of cell malignancy. Our study used LC-MS untargeted metabolomic approaches and real-time polymerase chain reaction (PCR) to characterize the molecular changes induced by a specific moderate uniaxial stretch regimen (i.e., 24h-1Hz, cyclic stretch 0,5% elongation) on SAOS-2 osteosarcoma cells. Differential metabolic pathway analysis revealed that the mechanical stimulation induces a down-regulation of both glycolysis and the tricarboxylic acid (TCA) cycle. At the same time, the amino acid metabolism was found to be dysregulated, with the mechanical stimulation enhancing glutaminolysis and reducing the methionine cycle. Our findings showed that cell metabolism and oxidative defense are tightly intertwined in mechanically stimulated cells. On the one hand, the mechano-induced disruption of the energy cell metabolism was found correlated with an antioxidant glutathione (GSH) depletion and an accumulation of reactive oxygen species (ROS). On the other hand, we showed that a moderate stretch regimen could disrupt the cytoprotective gene transcription by altering the expression levels of manganese superoxide dismutase (SOD1), Sirtuin 1 (SIRT1), and NF-E2-related factor 2 (Nrf2) genes. Interestingly, the cyclic applied strain could induce a cytotoxic sensitization (to the doxorubicin-induced cell death), suggesting that mechanical signals are integral regulators of cell cytoprotection. Hence, focusing on the mechanosensitive system as a therapeutic approach could potentially result in more effective treatments for osteosarcoma in the future.